Influencer marketing unlocked: Understanding the value chains driving the creator economy - Libai, Barak; Rosario, Ana Babić; Beichert, Maximilian; Donkers, Bas; Haenlein, Michael; Hofstetter, Reto; Kannan, P. K.; van der Lans, Ralf; Lanz, Andreas; Li, H. Alice; Mayzlin, Dina; Muller, Eitan; et al. (Journal of the Academy of Marketing Science, 2025)
Abstract As influencer marketing evolves into a dominant force in the marketing landscape, it necessitates a deeper theoretical exploration to understand its strategic implementations and impacts. This article examines the dynamics of influencer marketing within the growing creator economy, emphasizing the interactions among firms, influencers, followers, and digital platforms. We introduce a novel, equity-driven framework that analyzes how influencers contribute to customer equity, how influencers manage and leverage the value from their followers, and how platforms maximize the value from their users. We detail the complex relationships and value exchanges within the influencer marketing ecosystem, highlighting the challenges of measuring the return on investment and influencers’ strategic use of content to maintain authenticity and influence. By synthesizing diverse academic literature and current industry practices, this manuscript provides a comprehensive overview of the mechanisms of value creation and exchange in influencer marketing, offers strategic implications for marketers aiming to optimize their influencer engagements, and outlines future work in the form of the eleven “INFLUENCERS” research directions.